Kemampuan penalaran matematis siswa dalam menyelesaikan soal cerita - Nurul Dewi Cahyani; Teni Sritresna (Institut Pendidikan Indonesia, 2023)
AbstractThis research is motivated by students' reasoning abilities that are still low in solving math word problems. Students still have difficulty in giving proper reasons for a problem that has been done and confusion in giving conclusions about a statement. Even reasoning skills should be needed when students solve a problem because then students will easily apply them in solving a problem. This study aims to analyze students' mathematical reasoning abilities in solving word problems. This research uses a qualitative research approach with a descriptive research type. The subjects in this study were 6 students of class VIII-C of SMP Negeri 1 Kadungora who were selected from the results of the initial test of mathematical reasoning abilities, namely 3 students with high reasoning abilities, 1 student with moderate reasoning abilities, and 2 students with low reasoning abilities. The results of this study are 1) Students with high reasoning abilities in solving word problems, namely S-2 and S-3 are able to fulfill the four indicators of reasoning. While S-1 is able to fulfill three indicators of reasoning. 2) Students with moderate reasoning abilities in solving word problems are able to fulfill two reasoning indicators, namely S-4. 3) Students with low reasoning abilities in solving word problems are only able to fulfill one reasoning indicator, namely S,-5, and S-6. Abstrak Penelitian ini dilatarbelakangi oleh kemampuan penalaran siswa yang masih rendah dalam memecahkan soal cerita matematika. Siswa masih kesulitan dalam memberikan alasan yang tepat terhadap suatu permasalahan yang telah dikerjakan serta kebingungan dalam memberikan kesimpulan terhadap suatu pernyataan. Padahal seharusnya kemampuan penalaran sangat dibutuhkan ketika siswa memecahkan suatu permasalahan, karena dengan begitu siswa akan mudah menerapkannya dalam menyelesaikan suatu permasalahan. Penelitian ini bertujuan untuk menganalisis kemampuan penalaran matematis siswa dalam menyelesaikan soal cerita. Penelitian ini menggunakan pendekatan penelitian kualitatif dengan jenis penelitian deskriptif. Subjek dalam penelitian ini sebanyak 6 siswa kelas VIII-C SMP Negeri 1 Kadungora yang dipilih dari hasil tes awal kemampuan penalaran matematis yaitu 3 siswa dengan kemampuan penalaran tinggi, 1 siswa dengan kemampuan penalaran sedang, dan 2 siswa dengan kemampuan penalaran rendah. Hasil dari penelitian ini adalah: 1) Siswa dengan kemampuan penalaran tinggi dalam menyelesaikan soal cerita yaitu S-2 dan S-3 mampu memenuhi empat indikator penalaran. Sedangkan S-1 mampu memenuhi tiga indikator penalaran. 2) Siswa dengan kemampuan penalaran sedang dalam menyelesaikan soal cerita mampu memenuhi dua indikator penalaran yaitu S-4. 3) Siswa dengan kemampuan penalaran rendah dalam menyelesaikan soal cerita hanya mampu memenuhi satu indikator penalaran yaitu S-5 dan S-6.